Electronic structure and transport properties of antiferromagnetic double perovskite Y2AlCrO6. Issue 84 (26th August 2016) - Das, Indrani; Chanda, Sadhan; Saha, Sujoy; Dutta, Alo; Banerjee, Sourish; Bandyopadhyay, Sudipta; Sinha, T. P.
Abstract : The antiferromagnetic G-type magnetic ordering in Y2 AlCrO6 (YAC) has been investigated by the electronic band structure calculations and successive experiments. Abstract : The antiferromagnetic G-type magnetic ordering in Y2 AlCrO6 (YAC) has been investigated by electronic band structure calculations. The material is synthesised by a sol–gel technique and the electronic structure calculations are initiated by the experimental lattice parameters, obtained from the Rietveld refinement of the X-ray diffraction data. The Rietveld refinement shows that the room-temperature crystal structure of YAC is monoclinic with the space group P 21 / n, and contains an ordered array of alternating AlO6 and CrO6 octahedra tilted along the three pseudocubic axes according to the Glazer notation a − a − b + . The Raman spectrum of the sample is observed for P 21 / n symmetry. The field cooled and zero field cooled measurements of the sample are performed at a magnetic field of 100 Oe in the temperature range from 5 to 300 K. The temperature dependent magnetization shows the anti-ferromagnetic ordering of Cr ions in YAC. The calculated magnetic moment is well matched with the experimental magnetic moment and suggests the 3+ oxidation state of Cr with the canted alignment of its spin. The octahedral co-ordination of Cr 3+ ions in YAC is confirmed from the photoluminescence spectrum. The band gap obtained from the diffuse reflectance measurements shows the semiconducting nature of the material. To observe the effect of grains, grain-boundaries and electrodes in the conduction process, the dielectric relaxation of YAC has been investigated using alternating current impedance spectroscopy in the frequency range from 50 Hz to 5 MHz as a function of temperature. An electrical equivalent circuit consisting of the resistance and the constant phase element is used to explain the impedance data. The observed results are used to discuss the effect of substitution of Cr by Al in the parent compound YCrO3 .